Determinación de azúcares reductores y ph en heces de preescolares como indicadores de intolerancia a la lactosa - Loján Bermeo, Adriana del Cisne (2015)
Wrong absorption of sugars is given by the reduction or absence of digestive enzymes that are responsible for hydrolyzing the disaccharides, mainly lactose; this alteration occurs frequently, becoming a health problem that is rising, 50% of the world's population suffers from this digestive disorder and can vary from a population to another. The present study was conducted in order to determine the pH and sugar reducers in stool samples of children less than 5 years-old, as indicators of lactose intolerance. In this research, it was determined the sugars in feces of preschool children through application of colorimetric method; evaluation of pH in feces of preschoolers to applying test strips and the determination of the ratio of sugars and acid pH as an indicator of wrong absorption, lactose in pre-school children investigated. The research is descriptive and cross-sectional, in which 100 fecal samples of the children who attend the center of Social support "San Juan Bosco" from the city of Loja were processed. The presence of reducing sugars was detected in a 45% and an acid pH in 49% of the processed samples, demonstrating a significant direct relationship as an indicator of deficiency of digestive enzymes; It is important, to note that new studies must carried out using different techniques for the determination of reducing sugars and perform the comparison of these techniques. KEYWORDS: Reducing sugars, pH, fecal samples, lactose intolerance, preschoolers.